ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTEGRITAS LAPORAN KEUANGAN PERUSAHAAN YANG TERDAFTAR DI CORPORATE GOVERNANCE PERCEPTION INDEX - Siti Nur Farida; Wiwik Fitria Ningsih; Muhammad Rijalus Sholihin (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2025)
This study aimed to empirically examine the influence of audit tenure, earnings management, and good corporate governance on the integrity of financial statements of companies listed on the Corporate Governance Perception Index (CGPI) for the 2019-2023 period. This study was based on the importance of financial statement integrity in reflecting the company's actual financial condition, as well as the phenomenon of financial statement manipulation that is still found in companies with good governance predicates. The population used was companies listed on the CGPI and there were 6 companies as samples selected using a purposive sampling technique. The results showed that partially audit tenure does not affect the integrity of financial statements, earnings management also does not affect the integrity of financial statements, while good corporate governance does affect the integrity of financial statements. Simultaneously, audit tenure, earnings management, and good corporate governance affect the integrity of financial statements